Hypoglycemia, Arrythmia and Mortality in Diabetes, an underestimated risk? - Bartosz Kasperek; Patrycja Tymoszuk; Katarzyna Augustowska; Agata Żak-Gontarz; Rafał Sierzpowski; Agnieszka Protasiuk; Laura Loryś; Klaudia Klimczak; Kamila Budzyńska (Quality in Sport)
Introduction and purpose